2022
DOI: 10.1609/aaai.v36i2.20065
|View full text |Cite
|
Sign up to set email alerts
|

Debiased Batch Normalization via Gaussian Process for Generalizable Person Re-identification

Abstract: Generalizable person re-identification aims to learn a model with only several labeled source domains that can perform well on unseen domains. Without access to the unseen domain, the feature statistics of the batch normalization (BN) layer learned from a limited number of source domains is doubtlessly biased for unseen domain. This would mislead the feature representation learning for unseen domain and deteriorate the generalizaiton ability of the model. In this paper, we propose a novel Debiased Batch Normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…After obtaining initial data points, Bayesian optimization (BO) was employed for active learning. All experimental results were standardized to have zero mean and unit variance, a step crucial for efficient Gaussian Process (GP) modeling . A holistic illustration of this iterative decision-making scheme of BO can be seen in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After obtaining initial data points, Bayesian optimization (BO) was employed for active learning. All experimental results were standardized to have zero mean and unit variance, a step crucial for efficient Gaussian Process (GP) modeling . A holistic illustration of this iterative decision-making scheme of BO can be seen in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…All experimental results were standardized to have zero mean and unit variance, a step crucial for efficient Gaussian Process (GP) modeling. 28 A holistic illustration of this iterative decision-making scheme of BO can be seen in Figure 3. A GP with a Radial Basis Function (RBF) kernel was chosen for surrogate modeling.…”
Section: Initial Sampling Strategymentioning
confidence: 99%
“…To solve the above problems, [17] propose a novel method called the relevanceaware mixture of experts (RaMoE), using an effective voting-based mixture mechanism to dynamically leverage source domains' diverse characteristics to improve the model's generalization. [18] proposed a novel Debiased Batch Normalization via Gaussian Process approach (GDNorm) for generalizable person ReID, which models the feature statistic estimation from BN layers as a dynamically self-refining Gaussian process to alleviate the bias to unseen domain for improving the generalization. [19] found that the presence of Noisy Annotation (NA) will lead to the effect of noisy annotations on the constructed dataset, To solve the problem, a novel method for robust Visible-Infrared person re-identification, termed Du-Ally Robust Training (DART) was proposed.…”
Section: Short-term Person Re-identificationmentioning
confidence: 99%
“…Choi et al adopted the batch-instance normalization layers trained with the meta-learning strategy to avoid the overfitting to the source domain (Choi et al 2021). Liu et al defined a hybrid domain composed of the datasets from multiple domains, and trained the dataset in the hybrid domain with an ensemble of other batch normalization parameters to encourage the generalization capability (Liu et al 2022). However, these methods were devised for re-identification and cannot be directly applied to the person search task combined with the addition person detection.…”
Section: Domain Generalizationmentioning
confidence: 99%